2012
DOI: 10.1016/j.appet.2011.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Association between food marketing exposure and adolescents’ food choices and eating behaviors

Abstract: The present study examined associations between food marketing exposure and adolescents' food choices and reported consumption of energy-dense and nutrient-poor (EDNP) foods. A cross-sectional survey of 12,188 Australian secondary students aged 12-17 years was conducted, using a web-based self-report questionnaire. Measures included students' level of exposure to commercial television and non-broadcast types of food marketing, whether they had tried a new product or requested a product they had seen advertised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 23 publications
7
109
0
4
Order By: Relevance
“…As such, the strength of the association would have been attenuated. Similar trends were seen in the following studies when children self-reported exposure to food marketing (either on TV, print, on public transport, at school or digitally) and their usual food intake and/or purchase requests for promoted products [47][48][49].…”
Section: Observational Evidencesupporting
confidence: 58%
See 3 more Smart Citations
“…As such, the strength of the association would have been attenuated. Similar trends were seen in the following studies when children self-reported exposure to food marketing (either on TV, print, on public transport, at school or digitally) and their usual food intake and/or purchase requests for promoted products [47][48][49].…”
Section: Observational Evidencesupporting
confidence: 58%
“…This pattern was further shown in another Australian study (n=12,188, 12-17 years) [49]. As children's exposure to both commercial TV and non-broadcast advertising increased so too did their intakes of commonly advertised foods or likelihood of requesting or trying advertised foods (all p<0.001).…”
Section: Experimental Studies Using Premium Offersmentioning
confidence: 56%
See 2 more Smart Citations
“…Exposure to commercial advertising of snacks and the extent of watching TV programs was associated with a higher likelihood of serving fast foods and sweets, in both children and adults [11,12].…”
Section: Introductionmentioning
confidence: 99%